Conflict abroad and political trust at home evidence from a natural experiment - Klymak, M; Vlandas, T (Cambridge University Press, 2025)
Do conflicts abroad affect trust at home? While we know that conflicts impact trust in warring countries, we lack evidence on whether people in neighbouring, but non-involved, countries are also affected. We address this question in the case of Russia’s invasion of Ukraine in February 2022, which represented a large shock to the security and economy of European countries. Our identification strategy uses the overlap between the timing of the Russian invasion and the European Social Survey fieldwork in eleven European countries. We find that the invasion increased respondents’ trust in their country’s politicians, political parties, and national parliaments, as well as satisfaction with the government. Further analyses using other surveys and previous conflicts suggest this effect depends on proximity to the conflict and the political regimes of the attacked country. These findings contribute to our understanding of the complex and indirect effects of conflicts on domestic political trust.